2020
DOI: 10.1088/1555-6611/ab6027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laser-activated bleaching with 810 nm and 980 nm diode lasers on enamel micro-hardness; an in vitro study

Abstract: The aim of this study was to assess the micro-hardness of treated enamel with 810 nm and 980 nm diode lasers and to compare it with a conventional bleaching process.A sample of 45 caries-free human premolar teeth were selected. The enamel surfaces were completely polished. The crown portion of each tooth was then sectioned with a diamond disk, at dimensions of 3 × 3 × 3 mm. These sections were embedded in acrylic resin. The initial micro-hardness was determined by Vickers hardness apparatus at a vertical load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…Mushashae et al [21] and Kabbach et al [22] mentioned the duration of exposure to bleaching agent as a paramount factor in the reduction of enamel microhardness in addition to other factors such as the bleaching agent pH and concentration, so it seems that the higher concen-tration of hydrogen peroxide and longer exposure duration in group 3 compared to other groups is another cause for reduction of microhardness. In contrast to the current study, Saati et al [23] reported that Vickers microhardness of enamel after bleaching with Opalescence Boost PF did not change significantly compared to the other group that laser-assisted bleaching was done by using a diode laser. Using bleaching gel with high concentrations of hydrogen peroxide (35% to 50%) combined with a light source such as QTH lamp, diode laser, argon laser, or LED during office bleaching is suggested to decrease bleaching time.…”
Section: Discussioncontrasting
confidence: 99%
“…Mushashae et al [21] and Kabbach et al [22] mentioned the duration of exposure to bleaching agent as a paramount factor in the reduction of enamel microhardness in addition to other factors such as the bleaching agent pH and concentration, so it seems that the higher concen-tration of hydrogen peroxide and longer exposure duration in group 3 compared to other groups is another cause for reduction of microhardness. In contrast to the current study, Saati et al [23] reported that Vickers microhardness of enamel after bleaching with Opalescence Boost PF did not change significantly compared to the other group that laser-assisted bleaching was done by using a diode laser. Using bleaching gel with high concentrations of hydrogen peroxide (35% to 50%) combined with a light source such as QTH lamp, diode laser, argon laser, or LED during office bleaching is suggested to decrease bleaching time.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, enamel surface microhardness decreased after bleaching in all the study groups, consistent with a study by Mondelli et al 6 , in which enamel microhardness decreased after in-office bleaching with gels containing different concentrations of hydrogen peroxide (15%, 25%, and 35%). Saati et al 11 , too, showed a decreased enamel microhardness in samples bleached with 40% hydrogen peroxide alone or in association with a diode laser with 810-and 980-nm wavelengths.…”
Section: Discussionmentioning
confidence: 97%
“…When the material is mixed, fluoride appears at 1.1% concentration, and potassium nitrate appears at 3% concentration. This fluoride concentration can prevent a decrease in enamel surface microhardness to some extent 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations